2007
DOI: 10.14723/tmrsj.32.963
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of Stainless Steel Bipolar Plates in PEFC

Abstract: Stainless steels are one of the most promising materials as bipolar plates for polymer electrolyte membrane fuel cells (PEFCs). In use of stainless steel bipolar plates, however, corrosion and corrosion induced degradation of cell performance are anticipated. In the present study, corrosion behavior of SUS 304 and 31 OS stainless steels was investigated through polarization tests in the simulated PEFC environment (0.05M NazS04 (pH 2.3) + 2 ppm F solution at 353 K), contact resistance measurement between steels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The most extensively studied applicant stainless steels (SSs) have also been verified and cast-off as BPPs by numerous researchers, who reported that corrosion expanse is slight and PEM FC output is steady even after 1000 h of operation. , However, unfortunately, it was thought that due to its massive weight, it could be a severe delinquent in light of transportation utilization. Along with these limitations, aluminum (Al) is regarded as one of the most promising materials for its renewal functions, and some of its remarkable facilities, such as high electrical and fatigue resistance, high power, recyclability, thermal conductivity, low density, low price, and lightness. It seems to be the Al BPP maximum that diminishes 65% of the heaviness compared with the SS BPPs.…”
Section: Introductionmentioning
confidence: 99%
“…The most extensively studied applicant stainless steels (SSs) have also been verified and cast-off as BPPs by numerous researchers, who reported that corrosion expanse is slight and PEM FC output is steady even after 1000 h of operation. , However, unfortunately, it was thought that due to its massive weight, it could be a severe delinquent in light of transportation utilization. Along with these limitations, aluminum (Al) is regarded as one of the most promising materials for its renewal functions, and some of its remarkable facilities, such as high electrical and fatigue resistance, high power, recyclability, thermal conductivity, low density, low price, and lightness. It seems to be the Al BPP maximum that diminishes 65% of the heaviness compared with the SS BPPs.…”
Section: Introductionmentioning
confidence: 99%